2013
DOI: 10.1088/0957-4484/24/12/125702
|View full text |Cite
|
Sign up to set email alerts
|

Switching of ferroelectric liquid crystal doped with cetyltrimethylammonium bromide-assisted CdS nanostructures

Abstract: Large scale high yield cadmium sulfide (CdS) nanowires with uniform diameter were synthesized using a rapid and simple solvo-chemical and hydrothermal route assisted by the surfactant cetyltrimethylammonium bromide (CTAB). Unique CdS nanowires of different morphologies could be selectively produced by only varying the concentration of CTAB in the reaction system with cadmium acetate, sulfur powder and ethylenediamine. We obtained CdS nanowires with diameters of 64-65 nm and lengths of up to several micrometers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…[ 1,2 ] The incorporation of various nanomaterials into liquid crystals (LCs), and the complexity of their interaction, have recently attracted much interest. [3][4][5][6][7][8][9][10][11][12] The addition of nanoparticles (NPs) to liquid crystals produces composite materials with additional functionality, and tunable optic, electric, magnetic, or electrooptic properties. Both molecular and macroscopic bulk properties are modifi ed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1,2 ] The incorporation of various nanomaterials into liquid crystals (LCs), and the complexity of their interaction, have recently attracted much interest. [3][4][5][6][7][8][9][10][11][12] The addition of nanoparticles (NPs) to liquid crystals produces composite materials with additional functionality, and tunable optic, electric, magnetic, or electrooptic properties. Both molecular and macroscopic bulk properties are modifi ed.…”
mentioning
confidence: 99%
“…[ 3,4,[8][9][10] Recently, 1D nanoparticles, such as nanowires, were found to be effective for increasing the orientational order of liquid crystalline systems. [ 11 ] Rajh et al compared the effects of nanowires, nanorods, and nanotubes; they concluded that, due to the small aspect ratio, the nanorods showed more compatibility than the other nanomaterials. [ 12 ] In addition, 2D graphene fl akes doped in NLCs have improved electrooptic switching and dielectric anisotropy.…”
mentioning
confidence: 99%
“…The resulting mixture was left to vigorous stir at 70°C for 3 hours to complete the whole reaction mechanism. We investigated that in our first set of experiment white precipitate was obtained, while next gray colored precipitate was (1) and calculated with the help of the following relation [24,[49][50]:…”
Section: Methodsmentioning
confidence: 99%
“…The viscosity (γ) was determined from the measured value of the Polarization (P s ) and the switching time (τ) using the following relation [24];…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation